DEVELOPMENT OF SPORTS PROGRAMS IN CHILDREN PENITENTIARY INSTITUTION (LEMBAGA PEMBINAAKHUSUS ANAK) FOR FULFILLMENT CHILDREN'S BASIC RIGHTS: A POLICY FORMULATION - Maesa Faisyal, - (Pendidikan Olahraga Sekolah Pasacasarjana Universitas Pendidikan Indonesia, 2022)
ABSTRACT Physical activity in the form of sports activities is part of the basic needs in daily life that can be done to improve physical fitness and efforts to fulfill basic human rights, including the basic rights of children who are perpetrators of criminal acts and are serving a period at Lembaga Pembinaan Khusus Anak (LPKA) which also has the same rights and must fulfill the same basic rights as children in general. The importance of sport in the context of behavior improvement, character growth, and human rights makes the development of sports programs in a country very important because it is also part of the national development process. The purpose of this research is to formulate a sports policy program that is by the basic rights of children that can be implemented at the LPKA Bandung to fulfill children's basic rights and exercise. This research method is descriptive qualitative with data collection techniques in the form of open questionnaires, interviews, and observations and secondary data in the form of qualitative documentation studies. After all the data and information have been collected, a sports policy draft will be formulated based on the sports policy formulation process model according to Charles O. Jones in Eterna (2021). The results showed that the formulation of the sports policy program implemented in LPKA Bandung was able to represent the fulfillment of children's basic rights where the development of sports policy at LPKA Bandung could have a very positive influence on the rehabilitation and coaching process so that after the inmates finished their sentence at LPKA they would return to society with high values of life skills, have a fair play character and can also open up future opportunities. Keywords: Sports policy, children's basic rights.